2014
DOI: 10.1002/jbm.b.33354
|View full text |Cite
|
Sign up to set email alerts
|

Gene delivery in tissue engineering and regenerative medicine

Abstract: As a promising strategy to aid or replace tissue/organ transplantation, gene delivery has been used for regenerative medicine applications to create or restore normal function at the cell and tissue levels. Gene delivery has been successfully performed ex vivo and in vivo in these applications. Excellent proliferation capabilities and differentiation potentials render certain cells as excellent candidates for ex vivo gene delivery for regenerative medicine applications, which is why multipotent and pluripotent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 246 publications
(425 reference statements)
0
13
0
Order By: Relevance
“…In this context, gene therapy targeted to VSMCs and ECs is a promising therapeutic approach for the targeted inhibition of mechanisms leading to the development of vascular pathologies or to post-intervention complications [5]. Furthermore, in vitro gene delivery to primary VSMCs and ECs can be employed for tissue engineering and regeneration applications [6], and in the study of gene function and of the general physiology of vascular tissues [7].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, gene therapy targeted to VSMCs and ECs is a promising therapeutic approach for the targeted inhibition of mechanisms leading to the development of vascular pathologies or to post-intervention complications [5]. Furthermore, in vitro gene delivery to primary VSMCs and ECs can be employed for tissue engineering and regeneration applications [6], and in the study of gene function and of the general physiology of vascular tissues [7].…”
Section: Introductionmentioning
confidence: 99%
“…Under the assumption that previous in vitro results are transferable to in vivo findings, we found that this limited expression level seems to be sufficient to induce NB, because of endogenous BMP‐2 release by nontransfected cells via the paracrine stimulation of cells by the gene‐activated surface within the initial 14 days postsurgery. By the gene therapeutic approach, transgene‐derived low amounts of BMP2 are produced after local transfection of cells which then can activate additional endogenous BMP2 production in non‐transfected target cells …”
Section: Discussionmentioning
confidence: 99%
“…Nonviral vectors are advantageous in that they do not tend to insert permanently into the host's genome. Furthermore, the host's immune response is not triggered at such high levels as has been observed for other approaches …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As all approaches introduced above demonstrated high efficiency and therapeutic potential, still some risks prevailed, which requires further improvement for safer and superior treatment (Evans & Huard, ). Although bone loss and bone fracture are not fatal, gene therapy might induce lethal side effects such as mutagenesis and unexpected immune responses, where requires the consideration of benefits, to minimize the risks, and to ensure the safety issues associated with gene therapy (Fang et al, ).…”
Section: Osteobiologic Materialsmentioning
confidence: 99%